1996
DOI: 10.1557/jmr.1996.0153
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and magnetic behavior of NiFe2O4 thin films

Abstract: Thin films of NiFe2O4 were deposited on SrTiO3 (001) and Y0.15Zr0.85O2 (yttria-stabilized zirconia) (001) and (011) substrates by 90°-off-axis sputtering. Ion channeling, x-ray diffraction, and transmission electron microscopy studies reveal that films grown at 600 °C consist of ∼300 Å diameter grains separated by thin regions of highly defective or amorphous material. The development of this microstructure is attributed to the presence of rotated or displaced crystallographic domains and is comparable to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 14 publications
7
58
0
Order By: Relevance
“…As an explanation for the higher M s observed in the thinner films, we consider the possibility for the structure to experience a transition to the normal spinel structure, where trivalent ions are only found in [B] [8] and Lüders et al [7] invoked the same argument to account for the observation of an enhanced magnetization of ultrathin NFO films. It is worth however to mention that, so far, no other evidence has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an explanation for the higher M s observed in the thinner films, we consider the possibility for the structure to experience a transition to the normal spinel structure, where trivalent ions are only found in [B] [8] and Lüders et al [7] invoked the same argument to account for the observation of an enhanced magnetization of ultrathin NFO films. It is worth however to mention that, so far, no other evidence has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, however, the saturation magnetization of ultrathin films of NiFe 2 O 4 has been found to be substantially larger than bulk magnetization [7]. This unexpected result has been attributed to the out-of-equilibrium atomic distribution resulting from growth conditions [7,8] although definite explanation remains to be settled.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies on films with antiphase boundaries have shown that high-temperature annealing results in grain growth and a reduction in antiphase boundary density. 56 A further crossover as a function of thickness from a logarithmic dependence to exponential temperature dependence of sheet resistance and stronger localization occurs for the thinnest films (e.g. Figure 7 (a) or (b) t =14.6 nm), and this normal-state resistance crossover is accompanied by a subsequent complete suppression of the superconducting transition.…”
Section: Transportmentioning
confidence: 92%
“…A large number of articles have recently reported various types of ferrite films prepared using different techniques. [1][2][3][4][5][6][7] Though the bulk properties of ferrites are fairly well understood, it is found that it has only rarely been possible to achieve all these properties when deposited in thin film form. Moreover, certain new phenomena have been noted in the case of thin films that are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…11 Another phenomenon that has been specific to ferrite thin films, has been the observation of a large high field susceptibility. 5,6 There have not been many systematic studies carried out in sputter deposited ferrite thin films to investigate the evolution of saturation magnetization and other magnetic properties, and to understand the reasons of their difference from bulk materials. We have recently reported some studies on the rf sputter deposited LiZn ferrite films of composition Li0 0.5Ϫx/2 Mn 0.1 Zn x Fe 2.35Ϫx/2 O 4 with xϭ0, 0.16, 0.32, and 0.48.…”
Section: Introductionmentioning
confidence: 99%